2020
DOI: 10.1093/heapol/czaa108
|View full text |Cite
|
Sign up to set email alerts
|

How ready is the system to deliver primary healthcare? Results of a primary health facility assessment in Enugu State, Nigeria

Abstract: Primary health centres are an effective means of achieving access to primary healthcare (PHC) in low- and middle-income countries. We assessed service availability, service readiness and factors influencing service delivery at public PHC centres in Enugu State, Nigeria. We conducted a cross-sectional study of 60 randomly selected public health centres in Enugu using the World Health Organization’s Service Availability and Readiness Assessment (SARA) survey. The most senior health worker available was interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 27 publications
4
30
1
Order By: Relevance
“…We found that, a number of higher-level facilities had an ambulance or other vehicle available. This is however different from what Ekenna et al [ 49 ] reported in Nigeria. In their study, none of the facilities surveyed had a functional ambulance.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…We found that, a number of higher-level facilities had an ambulance or other vehicle available. This is however different from what Ekenna et al [ 49 ] reported in Nigeria. In their study, none of the facilities surveyed had a functional ambulance.…”
Section: Discussioncontrasting
confidence: 97%
“…Although health centres and clinics had an average GSR of 78.0%, this is relatively higher than what was reported in Mongolia [ 45 ] and this indicates good service readiness. Variations in service readiness of different facilities have also been reported in Nigeria [ 46 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study, for instance, found that the availability of equipment for NCD interventions was generally good, and this should be viewed as a positive step forward. In Consistent with our current ndings, previous studies have also shown disparities in the availability of health care resources for the prevention and control of NCDs between levels of care, types of facilities, and their rural-urban locations [1,24,27]. These current ndings are important in that they further highlight that where NCDs health services are needed most by the populations (that is, at primary care, public and rural facilities), they are not always readily available in these settings.…”
Section: Discussionsupporting
confidence: 92%
“…It remains unclear how ready the health systems are to deliver quality CLD care in these settings. Several studies have examined the state of preparedness of health systems in LMICs to deliver general health services, specific disease services or primary health care in the context of universal health coverage [19][20][21][22]. Studies investigating preparedness for CLD services are however rare.…”
Section: Introductionmentioning
confidence: 99%